QTL Landscape for Oil Content in Brassica juncea: Analysis in Multiple Bi-Parental Populations in High and “0” Erucic Background - Rout, Kadambini; Yadav, Bal Govind; Yadava, Satish Kumar; Mukhopadhyay, Arundhati; Gupta, Vibha; Pental, Deepak; Pradhan, Akshay K. (Frontiers in Plant Science, 2018)
Increasing oil content in oilseed mustard (Brassica juncea) is a major breeding objective – more so, in the lines that have ‘0’ erucic acid content (<2% of the seed oil) as earlier studies have shown negative pleiotropic effect of erucic acid loci on the oil content, both in oilseed mustard and rapeseed. We report here QTL analysis of oil content in eight different mapping populations involving seven different parents - including a high oil content line J8 (~49%). The parental lines of the mapping populations contained wide variation in oil content and erucic acid content. The eight mapping populations were categorized into two sets – five populations with individuals segregating for erucic acid (SE populations) and the remaining three with zero erucic acid segregants (ZE populations). Meta-analysis of QTL mapped in individual SE populations identified nine significant C-QTL, with two of these merging most of the major oil QTL that colocalized with the erucic acid loci on the linkage groups A08 and B07. QTL analysis of oil content in ZE populations revealed a change in the landscape of the oil QTL compared to the SE populations, in terms of altered allelic effects and phenotypic variance explained by ZE QTL at the ‘common’ QTL and observation of ‘novel’ QTL in the ZE background. The important loci contributing to oil content variation, identified in the present study could be used in the breeding programmes for increasing the oil content in high erucic and ‘0’ erucic backgrounds.